(untitled) (Journal of Enam Medical College, 2016)
Nipah virus, a member of the genus Henipavirus, a new class of virus in the Paramyxoviridae family, has drawn attention as an emerging zoonotic virus in South-East and South Asian region. Case fatality rate of Nipah virus infection ranges from 4070% although it has been as high as 100% in some outbreaks. Many of the outbreaks were attributed to pigs consuming fruits, partially eaten by fruit bats, and transmission of infection to humans. In Bangladesh, Nipah virus infection was associated with contact with a sick cow, consumption of fresh date palm sap (potentially contaminated with pteropid bat saliva), and person-to-person transmission. In 2014, 18 cases of Nipah virus infection have been reported in Bangladesh, of which 9 cases died. In the most recent epidemic at least 6 people died out of nine cases due to Nipah virus infection in the remote northern Bangladesh in 2015. Human infections range from asymptomatic infection to fatal encephalitis. Some people can also experience atypical pneumonia and severe respiratory problems. The virus is detected by ELISA, PCR, immunofluoroscence assay and isolation by cell culture. Treatment is mostly symptomatic and supportive as the effect of antiviral drugs is not satisfactory, and an effective vaccine is yet to be developed. So the very high case fatality addresses the need for adequate and strict control and preventive measures. J Enam Med Col 2016; 6(2): 101-105